2018
DOI: 10.20944/preprints201806.0057.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Slight pH Fluctuations in the Gold Nanoparticle Synthesis Process Influence the Performance of the Citrate Reduction Method

Abstract: Gold nanoparticles (AuNPs) are currently under intense investigation for biomedical and biotechnology applications, thanks to their ease in preparation, stability, biocompatibility, multiple surface functionalities and size-dependent optical properties. The most commonly used method for AuNPs synthesis in aqueous solution is the reduction of tetrachloroauric acid (HAuCl4) with trisodium citrate. We observed variations in the pH and concentration of the gold colloidal suspension synthesized under standard condi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…Further, the thermodynamic description of adsorption of citric acid and dihydrogen citrate on Au (111) surface has been studied using electrochemical methods such as chronocoulometry and cyclic voltammetry comparing the adsorption of citrate at different pH 15 . The general observation was that the surface coverage increased three-fold as pH was raised from 1 to 3.In a recent study, the effect of thedecrease in pH from 5.3 to 4.7 resulted in the reduction of the AuNP concentrationby 46% 16 .…”
Section: Quantification Of Adsorbed and Dangling Citrate Ions On Goldmentioning
confidence: 97%
See 1 more Smart Citation
“…Further, the thermodynamic description of adsorption of citric acid and dihydrogen citrate on Au (111) surface has been studied using electrochemical methods such as chronocoulometry and cyclic voltammetry comparing the adsorption of citrate at different pH 15 . The general observation was that the surface coverage increased three-fold as pH was raised from 1 to 3.In a recent study, the effect of thedecrease in pH from 5.3 to 4.7 resulted in the reduction of the AuNP concentrationby 46% 16 .…”
Section: Quantification Of Adsorbed and Dangling Citrate Ions On Goldmentioning
confidence: 97%
“…As discussed earlier, under alkaline condition MSC ions convert into the TSC ions on AuNP surface. So, the varying pH has been known to be a crucial factor 16 affecting the concentration of citrate ions on AuNP surface which may also give a definitive evidence for mechanism of synthesis of AuNPs via Turkevich method. Thus, for understanding the quantification of citrate ions in alkaline condition, the pH of the purified Au-18 after re-dispersion in water was adjusted to 11.3 using 0.1 M sodium hydroxide in order to reduce citrate layers formed by hydrogen bonding between adsorbed citrate and free citrate 21 .…”
Section: Quantification Of Adsorbed and Dangling Citrate Ions On Goldmentioning
confidence: 99%
“…For the flow synthesis, there could have been variations in the pH in the formed aqueous droplets because of flow fluctuations by the pump during the process, as well as due to experimental inaccuracies. The study of Contreras-Trigo et al [41] has shown that small variation on the pH in the citrate reduction method (from 4.7 to 5.3) can alter the average particle size betweeñ 14.0 nm -15.5 nm, due to the shift on the gold complex and citrate species taking part in the reactions at different pH [23]. The pH of the solution could also be affected by reactant speciation in the initial part of the reactor where the solution temperature increases from room temperature to the target of 95 o C; the species of gold and citrate will be different than those expected at the final temperature (as the redistribution of the reactants among their various species is temperature-dependent) [42,43].…”
Section: Synthesis Of Gold Nanoparticles In Flowmentioning
confidence: 99%
“…These ndings suggest that the protonation of AuNPs essentially dominated the succeeding aggregation due to the suppression of negative charges on the AuNPs at pH 1.5. 32,33 This implied that the AuNPs might lose their detection capability under such circumstances because they directly entered the aggregation stage prior to initiating the informative visual sensing of analytes.…”
Section: Effect Of Ph Value On Protonation Of Aunpsmentioning
confidence: 99%